Effects of service-learning as opposed to traditional teaching-learning contexts: a pilot study with three different courses - Pinto, J. C.; Costa-Ramalho, Susana (Frontiers in Education, 2023)
Service-Learning (SL) is an innovative teaching-learning proposal with an increasingly wide application in higher education. Previous studies show its potential to generate positive personal, academic, social and citizenship outcomes among students who participate in it. But studies that help understand in depth its real impact, particularly in comparison with more traditional teaching-learning contexts, are still scarce. This study explores the effects of Service-Learning on 122 university students, who were attending Psychology (n=80), Social Work (SW; n=19) and Applied Foreign Languages (AFL; n=23) degree courses. These participants were organized into servicelearning and traditional teaching-learning groups and assessed on expectations and impact of the service-experience, development of social and civic skills, and life goals. Results show significant differences between pre-and post-tests in life goals, namely an increase in hedonistic and wellbeing goals for Psychology students, political, hedonistic, religious, personal development, and wellbeing goals for SW students, and social and wellbeing goals for AFL students. Students in Psychology and AFL increased their expectations with the service and students in the AFL developed more pro-social behaviors. These results are encouraging for the expansion of this transformative teaching-learning practice to courses of different scientific areas, although with some specificities, with the purpose of contributing to a more responsible, critical and participatory society in the creation of the common good.